Avaliação da atividade antioxidante e atividade antimicrobiana extratos de cascas de romãs (Punica granatum L.) submetidas a dois diferentes métodos de secagem - Marchi, Livia Benossi (2014)
The peel of pomegranate (Punica granatum L.) are considered fruit products, however have significant concentrations of polyphenols and flavonoids which may be used as antioxidants and antimicrobial agents. The drying process is of great importance and influence on the preservation of these products. The objective of this study was to evaluate the application of two drying methods: under glass and freeze-drying on the antioxidant and antimicrobial potential of aqueous and ethanol extracts of pomegranate peel. Pomegranates collected in local shops Maringa-Paraná-Brazil and were cleaned and sanitized. The shells were manually separated, washed, dried at room temperature and protected from light, stored in vacuum packaging and frozen at -20°C for analysis. In the drying oven peel samples were subjected to the dehydration process with air circulation at temperatures of 40°C, 50°C and 60°C (± 1°C) until the peel obtain water activity and humidity 0.3 with less than 3%. For lyophilization, pomegranate peels were processed in a lyophilizer for a period of 24 hours, whereas the same parameter activity and moisture to oven drying. Dry pomegranate peels were extracted with water and ethanol and evaluated for chemical composition, concentration of total phenolic compounds, antioxidant activity and evaluation of antimicrobial activity. The results showed that drying oven has a higher yield and economic feasibility shorter drying time, but the values of phenolics and antioxidant activity were significantly reduced.